Trends and low frequency variability of East Coast Lows in the twentieth century - Ji, Fei; Pepler, Acacia; Browning, Stuart; Evans, Jasona; Di Luca, Alejandro (Journal of Southern Hemisphere Earth System Science, 2018)

Distribution and (palaeo)ecological affinities of the main Spiniferites taxa in the mid-high latitudes of the Northern Hemisphere - De Vernal, Anne; Eynaud, Frédérique; Henry, Maryse; Limoges, Audrey; Londeix, Laurent; Matthiessen, Jens; Marret, Fabienne; Pospelova, Vera; Radi, Taoufik; Rochon, André; Van Nieuwenhove, Nicolas; Zaragosi, Sébastien (Palynology, 2018)

Identification key for Pliocene and Quaternary Spiniferites taxa bearing intergonal processes based on observations from estuarine and coastal environments - Limoges, Audrey; Londeix, Laurent; Mertens, Kenneth Neil; Rochon, André; Pospelova, Vera; Cuéllar, Tomasa; De Vernal, Anne (Palynology, 2018)

The dinoflagellate cyst genera Achomosphaera Evitt 1963 and Spiniferites Mantell 1850 in Pliocene to modern sediments: a summary of round table discussions - Mertens, Kenneth Neil; Van Nieuwenhove, Nicolas; Gurdebeke, Pieter R.; Aydin, Hilal; Bogus, Kara; Bringué, Manuel; Dale, Barrie; De Schepper, Stijn; De Vernal, Anne; Ellegaard, Marianne; Grothe, Arjen; Gu, Haifeng; et al. (Palynology, 2018)

Allocation Mechanisms of Non-Structural Carbohydrates of Robinia pseudoacacia L. Seedlings in Response to Drought and Waterlogging - Yang, Bin; Peng, Changhui; Harrison, Sandy P.; Wei, Hua; Wang, Han; Zhu, Qiuan; Wang, Meng (Forests, 2018)
Climate change is likely to lead to an increased frequency of droughts and floods, both of which are implicated in large-scale carbon allocation and tree mortality worldwide. Non-structural carbohydrates (NSCs) play an important role in tree survival under stress, but how NSC allocation changes in response to drought or waterlogging is still unclear. We measured soluble sugars (SS) and starch in leaves, twigs, stems and roots of Robinia pseudoacacia L. seedlings that had been subjected to a gradient in soil water availability from extreme drought to waterlogged conditions for a period of 30 days. Starch concentrations decreased and SS concentrations increased in tissues of R. pseudoacacia seedlings, such that the ratio of SS to starch showed a progressive increase under both drought and waterlogging stress. The strength of the response is asymmetric, with the largest increase occurring under extreme drought. While the increase in SS concentration in response to extreme drought is the largest in roots, the increase in the ratio of SS to starch is the largest in leaves. Individual components of SS showed different responses to drought and waterlogging across tissues: glucose concentrations increased significantly with drought in all tissues but showed little response to waterlogging in twigs and stems; sucrose and fructose concentrations showed marked increases in leaves and roots in response to drought but a greater response to drought and waterlogging in stems and twigs. These changes are broadly compatible with the roles of individual SS under conditions of water stress. While it is important to consider the role of NSC in buffering trees against mortality under stress, modelling this behaviour is unlikely to be successful unless it accounts for different responses within organs and the type of stress involved.

A global strategy to mitigate the environmental impact of China’s ruminant consumption boom - Du, Yuanyuan; Ge, Ying; Ren, Yuan; Fan, Xing; Pan, Kaixuan; Lin, Linshan; Wu, Xu; Min, Yong; Meyerson, Laura A.; Heino, Mikko; Chang, Scott X.; Liu, Xiaozi; et al. (Nature Communications, 2018)
Abstract Rising demand for ruminant meat and dairy products in developing countries is expected to double anthropogenic greenhouse gas and ammonia emissions from livestock by 2050. Mitigation strategies are urgently needed to meet demand while minimizing environmental impacts. Here, we develop scenarios for mitigating emissions under local vs global supply policies using data from 308 livestock farms across mainland China, where emissions intensities are ~50% higher than those in developed nations. Intensification of domestic production and globalized expansion through increased trade result in reductions in global emissions by nearly 30% over a business-as-usual scenario, but at the expense of trading partners absorbing the associated negative externalities of environmental degradation. Only adoption of a mixed strategy combining global best-practice in sustainable intensification of domestic production, with increased green-source trading as a short-term coping strategy, can meet 2050 demand while minimizing the local and global environmental footprint of China’s ruminant consumption boom.

Development of a New TRIPLEX-Insect Model for Simulating the Effect of Spruce Budworm on Forest Carbon Dynamics - Liu, Zelin; Peng, Changhui; De Grandpré, Louis; Candau, Jean-Noël; Zhou, Xiaolu; Kneeshaw, Daniel (Forests, 2018)
The spruce budworm (SBW) defoliates and kills conifer trees, consequently affecting carbon (C) exchanges between the land and atmosphere. Here, we developed a new TRIPLEX-Insect sub-model to quantify the impacts of insect outbreaks on forest C fluxes. We modeled annual defoliation (AD), cumulative defoliation (CD), and tree mortality. The model was validated against observed and published data at the stand level in the North Shore region of Québec and Cape Breton Island in Nova Scotia, Canada. The results suggest that TRIPLEX-Insect performs very well in capturing tree mortality following SBW outbreaks and slightly underestimates current annual volume increment (CAI). In both mature and immature forests, the simulation model suggests a larger reduction in gross primary productivity (GPP) than in autotrophic respiration (Ra) at the same defoliation level when tree mortality was low. After an SBW outbreak, the growth release of surviving trees contributes to the recovery of annual net ecosystem productivity (NEP) based on forest age if mortality is not excessive. Overall, the TRIPLEX-Insect model is capable of simulating C dynamics of balsam fir following SBW disturbances and can be used as an efficient tool in forest insect management.

Precipitation characteristics and associated weather conditions on the eastern slopes of the Canadian Rockies during March–April 2015 - Thériault, Julie M.; Hung, Ida; Vaquer, Paul; Stewart, Ronald E.; Pomeroy, John W. (Hydrology and Earth System Sciences, 2018)
Abstract. Precipitation events that bring rain and snow to the Banff–Calgary area of Alberta are a critical aspect of the region's water cycle and can lead to major flooding events such as the June 2013 event that was the second most costly natural disaster in Canadian history. Because no special atmospheric-oriented observations of these events have been made, a field experiment was conducted in March and April 2015 in Kananaskis, Alberta, to begin to fill this gap. The goal was to characterize and better understand the formation of the precipitation at the surface during spring 2015 at a specific location in the Kananaskis Valley. Within the experiment, detailed measurements of precipitation and weather conditions were obtained, a vertically pointing Doppler radar was deployed and weather balloons were released. Although 17 precipitation events occurred, this period was associated with much less precipitation than normal (−35 %) and above-normal temperatures (2.5 ∘C). Of the 133 h of observed precipitation, solid precipitation occurred 71 % of the time, mixed precipitation occurred 9 % and rain occurred 20 %. An analysis of 17 504 precipitation particles from 1181 images showed that a wide variety of crystals and aggregates occurred and approximately 63 % showed signs of riming. This was largely independent of whether flows aloft were upslope (easterly) or downslope (westerly). In the often sub-saturated surface conditions, hydrometeors containing ice occurred at temperatures as high as 9 ∘C. Radar structures aloft were highly variable with reflectivity sometimes >30 dBZe and Doppler velocity up to −1 m s−1, which indicates upward motion of particles within ascending air masses. Precipitation was formed in this region within cloud fields sometimes having variable structures and within which supercooled water at least sometimes existed to produce accreted particles massive enough to reach the surface through the relatively dry sub-cloud region.

Contrasting Soil Bacterial Community, Diversity, and Function in Two Forests in China - Wei, Hua; Peng, Changhui; Yang, Bin; Song, Hanxiong; Li, Quan; Jiang, Lin; Wei, Gang; Wang, Kefeng; Wang, Hui; Liu, Shirong; Liu, Xiaojing; Chen, Dexiang; et al. (Frontiers in Microbiology, 2018)

Asymmetric responses of primary productivity to altered precipitation simulated by ecosystem models across three long-term grassland sites - Wu, Donghai; Ciais, Philippe; Viovy, Nicolas; Knapp, Alan K.; Wilcox, Kevin; Bahn, Michael; Smith, Melinda D.; Vicca, Sara; Fatichi, Simone; Zscheischler, Jakob; He, Yue; Li, Xiangyi; et al. (Biogeosciences, 2018)
Abstract. Field measurements of aboveground net primary productivity (ANPP) in temperate grasslands suggest that both positive and negative asymmetric responses to changes in precipitation (P) may occur. Under normal range of precipitation variability, wet years typically result in ANPP gains being larger than ANPP declines in dry years (positive asymmetry), whereas increases in ANPP are lower in magnitude in extreme wet years compared to reductions during extreme drought (negative asymmetry). Whether the current generation of ecosystem models with a coupled carbon–water system in grasslands are capable of simulating these asymmetric ANPP responses is an unresolved question. In this study, we evaluated the simulated responses of temperate grassland primary productivity to scenarios of altered precipitation with 14 ecosystem models at three sites: Shortgrass steppe (SGS), Konza Prairie (KNZ) and Stubai Valley meadow (STU), spanning a rainfall gradient from dry to moist. We found that (1) the spatial slopes derived from modeled primary productivity and precipitation across sites were steeper than the temporal slopes obtained from inter-annual variations, which was consistent with empirical data; (2) the asymmetry of the responses of modeled primary productivity under normal inter-annual precipitation variability differed among models, and the mean of the model ensemble suggested a negative asymmetry across the three sites, which was contrary to empirical evidence based on filed observations; (3) the mean sensitivity of modeled productivity to rainfall suggested greater negative response with reduced precipitation than positive response to an increased precipitation under extreme conditions at the three sites; and (4) gross primary productivity (GPP), net primary productivity (NPP), aboveground NPP (ANPP) and belowground NPP (BNPP) all showed concave-down nonlinear responses to altered precipitation in all the models, but with different curvatures and mean values. Our results indicated that most models overestimate the negative drought effects and/or underestimate the positive effects of increased precipitation on primary productivity under normal climate conditions, highlighting the need for improving eco-hydrological processes in those models in the future.

Improving the Explicit Prediction of Freezing Rain in a Kilometer-Scale Numerical Weather Prediction Model - Barszcz, Agnieszka; Milbrandt, Jason A.; Thériault, Julie M. (Weather and Forecasting, 2018)
Abstract A freezing rain event, in which the Meteorological Centre of Canada’s 2.5-km numerical weather prediction system significantly underpredicted the quantity of freezing rain, is examined. The prediction system models precipitation types explicitly, directly from the Milbrandt–Yau microphysics scheme. It was determined that the freezing rain underprediction for this case was due primarily to excessive refreezing of rain, originating from melting snow and graupel, in and under the temperature inversion of the advancing warm front ultimately depleting the supply of rain reaching the surface. The refreezing was caused from excessive collisional freezing between rain and graupel. Sensitivity experiments were conducted to examine the effects of a temperature threshold for collisional freezing and on varying the values of the collection efficiencies between rain and ice-phase hydrometeors. It was shown that by reducing the rain–graupel collection efficiency and by imposing a temperature threshold of −5°C, above which collisional freezing is not permitted, excessive rain–graupel collection and graupel formation can be controlled in the microphysics scheme, leading to an improved simulation of freezing rain at the surface.

Modeling Gross Primary Production of a Typical Coastal Wetland in China Using MODIS Time Series and CO2 Eddy Flux Tower Data - Kang, Xiaoming; Yan, Liang; Zhang, Xiaodong; Li, Yong; Tian, Dashuan; Peng, Changhui; Wu, Haidong; Wang, Jinzhi; Zhong, Lei (Remote Sensing, 2018)
How to effectively combine remote sensing data with the eddy covariance (EC) technique to accurately quantify gross primary production (GPP) in coastal wetlands has been a challenge and is also important and necessary for carbon (C) budgets assessment and climate change studies at larger scales. In this study, a satellite-based Vegetation Photosynthesis Model (VPM) combined with EC measurement and Moderate Resolution Imaging Spectroradiometer (MODIS) data was used to evaluate the phenological characteristics and the biophysical performance of MODIS-based vegetation indices (VIs) and the feasibility of the model for simulating GPP of coastal wetland ecosystems. The results showed that greenness-related and water-related VIs can better identify the green-up and the senescence phases of coastal wetland vegetation, corresponds well with the C uptake period and the phenological patterns that were delineated by GPP from EC tower (GPPEC). Temperature can explain most of the seasonal variation in VIs and GPPEC fluxes. Both enhanced vegetation index (EVI) and water-sensitive land surface water index (LSWI) have a higher predictive power for simulating GPP in this coastal wetland. The comparisons between modeled GPP (GPPVPM) and GPPEC indicated that VPM model can commendably simulate the trajectories of the seasonal dynamics of GPPEC fluxes in terms of patterns and magnitudes, explaining about 85% of GPPEC changes over the study years (p < 0.0001). The results also demonstrate the potential of satellite-driven VPM model for modeling C uptake at large spatial and temporal scales in coastal wetlands, which can provide valuable production data for the assessment of global wetland C sink/source.

Effect of Drought on Agronomic Traits of Rice and Wheat: A Meta-Analysis - Zhang, Jinmeng; Zhang, Shiqiao; Cheng, Min; Jiang, Hong; Zhang, Xiuying; Peng, Changhui; Lu, Xuehe; Zhang, Minxia; Jin, Jiaxin (International Journal of Environmental Research and Public Health, 2018)
Drought has been one of the most important limiting factors for crop production, which deleteriously affects food security worldwide. The main objective of the present study was to quantitatively assess the effect of drought on the agronomic traits (e.g., plant height, biomass, yield, and yield components) of rice and wheat in combination with several moderators (e.g., drought stress intensity, rooting environment, and growth stage) using a meta-analysis study. The database was created from 55 published studies on rice and 60 published studies on wheat. The results demonstrated that drought decreased the agronomic traits differently between rice and wheat among varying growth stages. Wheat and rice yields decreased by 27.5% and 25.4%, respectively. Wheat grown in pots showed greater decreases in agronomic traits than those grown in the field. Rice showed opposite growing patterns when compared to wheat in rooting environments. The effect of drought on rice increased with plant growth and drought had larger detrimental influences during the reproductive phase (e.g., blooming stage, filling stage, and maturity). However, an exception was found in wheat, which had similar decreased performance during the complete growth cycle. Based on these results, future droughts could produce lower yields of rice and wheat when compared to the current drought.

Variation in Soil Methane Fluxes and Comparison between Two Forests in China - Wei, Hua; Peng, Changhui; Liu, Shirong; Liu, Xiaojing; Li, Peng; Song, Hanxiong; Yuan, Minshu; Wang, Meng (Forests, 2018)
Methane (CH4) is a vital greenhouse gas with a 28-fold higher global warming potential than carbon dioxide when considering a molar basis for the time horizon of 100 years. Here, we investigated the variation of soil CH4 fluxes, soil physiochemical properties, and CH4-related bacteria community composition of two forests in China. We measured CH4 fluxes using static chambers and analyzed soil bacterial communities using next-generation high-throughput sequencing in a temperate broad-leaved deciduous forest at Baotianman Nature Reserve (TBDF-BTM) and a tropical rainforest at Jianfengling National Natural Reserve (TRF-JFL). Our results showed that the soils from both sites were CH4 sinks. Significant variation in soil CH4 fluxes was found at TBDF-BTM exclusively, while no seasonal variation in the CH4 uptake was observed at TRF-JFL. The CH4 fluxes at TBDF-BTM were substantially higher than those at TRF-JFL during all seasons. One genus of methanotrophs and three genera of methylotrophs were detected at both sites, though they had no direct relationship with soil CH4 fluxes. Water-filled pore space and soil total carbon content are the main factors controlling the soil CH4 fluxes at TBDF-BTM. At TRF-JFL, the soil CH4 fluxes showed no significant correlations with any of the soil properties. This study improves our understanding of soil CH4 fluxes and their influencing factors in forests in different climatic zones and provides a reference for future investigation of forest soil CH4 fluxes, the forest ecosystem carbon cycle, and the forest CH4 model.

Recoupling Industrial Dairy Feedlots and Industrial Farmlands Mitigates the Environmental Impacts of Milk Production in China - Fan, Xing; Chang, Jie; Ren, Yuan; Wu, Xu; Du, Yuanyuan; Xu, Ronghua; Liu, Dong; Chang, Scott X.; Meyerson, Laura A.; Peng, Changhui; Ge, Ying (Environmental Science & Technology, 2018)

Biochar amendment decreases soil microbial biomass and increases bacterial diversity in Moso bamboo ( Phyllostachys edulis ) plantations under simulated nitrogen deposition - Li, Quan; Lei, Zhaofeng; Song, Xinzhang; Zhang, Zhiting; Ying, Yeqing; Peng, Changhui (Environmental Research Letters, 2018)

Interactive Effect of Radioactive and Heavy-MetalContamination on Soil Enzyme Activityin a Former Uranium Mine - Yang, Gang; Dong, Faqin; Liu, Mingxue; Nie, Xiaoqin; Zong, Meirong; Peng, Changhui; Chen, Huai; Wei, Hongfu; Wang, Pingping; Zhang, Wei (Polish Journal of Environmental Studies, 2018)

The impact of future atmospheric circulation changes over the Euro-Atlantic sector on urban PM2.5 concentrations - Messori, Gabriele; Van Wees, Dave; Pausata, Francesco S.R.; Navarro, Juan C. Acosta; Hannachi, Abdel; Dentener, Frank J. (Tellus B: Chemical and Physical Meteorology, 2018)

Late Holocene Sea Surface Instabilities in the Disko Bugt Area, West Greenland, in Phase With δ18 O Oscillations at Camp Century - Allan, Estelle; De Vernal, Anne; Knudsen, Mads Faurschou; Hillaire‐Marcel, Claude; Moros, Matthias; Ribeiro, Sofia; Ouellet‐Bernier, Marie‐Michèle; Seidenkrantz, Marit‐Solveig (Paleoceanography and Paleoclimatology, 2018)
Abstract Palynological analyses of sediment core MSM343310 from Disko Bugt (68°38′861°N, 53°49′493°W) document decadal‐ to centennial‐scale variability of sea surface conditions during the last ~ 3,600 years. Dinocyst fluxes (>10 4 cysts/cm 2 yr −1 ) indicate a very high productivity. Dinocyst assemblages dominated by Islandinium minutum , Brigantedinium spp., Islandinium ? cezare , and the cyst of Pentapharsodinium dalei suggest low surface salinity and marked shifts in summer sea surface temperature. The application of the modern analog technique to dinocyst assemblages, using an updated reference data set with new sites from the West Greenland margin, led to reconstruct decadal‐centennial‐scale variations in sea surface salinity and temperature, in phase with the δ 18 O variations in the Camp Century ice core. At ~ 1.5 ka BP, the seasonal sea ice cover records an important regime change, from winter‐only sea ice to more unstable conditions marked by successive cooling pulses with sea ice cover of up to 8 months/yr. The data suggest a close relationship between hydrographic conditions and regional climate over Greenland. Our record shows variations with a mean 200 years periodicity until ~2 ka BP, which supports the hypothesis of climate variations driven by solar variability. After 1.5 ka BP, our data show a variability characterized by a 60–70 year periodicity, which suggests linkages with the Atlantic Multidecadal Oscillation and southwestward migration of the atmospheric polar front. The most recent part of the record, from ~1900 CE to 2007 CE, is characterized by assemblages reflecting warmer surface conditions and reduced sea ice cover. , Key Points Sea surface salinity changes are used as indicators of fresh‐meltwater events and sea ice cover as a diagnostic feature of regional climate Changing sea surface conditions from Disko Bugt are closely related with regional climate over Greenland A marked change in surface waters at about 1.5 ka BP corresponds to enhanced sea ice cover and the onset of unstable conditions

Maximum Likelihood Estimation of the Markov-Switching GARCH Model Based on a General Collapsing Procedure - Augustyniak, Maciej; Boudreault, Mathieu; Morales, Manuel (Methodology and Computing in Applied Probability, 2018)

The response of the net primary production of Moso bamboo forest to the On and Off-year management: A case study in Anji County, Zhejiang, China - Chen, Shulin; Jiang, Hong; Cai, Zhijian; Zhou, Xiaolu; Peng, Changhui (Forest Ecology and Management, 2018)

Environmental forcing on the flux of organic-walled dinoflagellate cysts in recent sediments from a subtropical lagoon in the Gulf of California - Cuellar-Martinez, Tomasa; Alonso-Rodríguez, Rosalba; Ruiz-Fernández, Ana Carolina; De Vernal, Anne; Morquecho, Lourdes; Limoges, Audrey; Henry, Maryse; Sanchez-Cabeza, Joan-Albert (Science of The Total Environment, 2018)

Controls of soil and aggregate‐associated organic carbon variations following natural vegetation restoration on the L oess P lateau in C hina - Deng, Lei; Kim, Dong‐Gill; Peng, Changhui; Shangguan, Zhouping (Land Degradation & Development, 2018)
Abstract Natural vegetation restoration can enhance soil organic carbon (SOC) sequestration, but the mechanisms and control factors underlying SOC sequestration are still unknown. The objectives of the study are to quantify the temporal variation of soil and aggregate‐associated organic carbon (OC) and identify factors controlling the variation following natural vegetation restoration after farmland abandonment. We collected soils from sites having 5, 30, 60, 100, and 160 years of a natural vegetation restoration chronosequence after farmland abandonment in the Loess Plateau, China. The results showed that natural vegetation restoration increased macroaggregates (0.25–2 mm; 46.6% to 73.9%), SOC (2.27 to 9.81 g kg −1 ), and aggregate OC (7.33 to 36.98 g kg −1 ) in the top 20‐cm soil compared with abandoned farmland, and the increases mainly occurred in the early stage (<60 years). The increase of SOC was contributed by OC accumulated in macroaggregates (0.25–2 mm) rather than microaggregates (≤0.25 mm). Moreover, SOC sequestration in the topsoil (0–10 cm) was mainly determined by fine root biomass (FR), labile organic carbon (LOC), and microbial biomass carbon (MBC). And in the subsoil (10–20 cm), SOC sequestration was mainly determined by the proportion of macroaggregates. The results suggest that natural vegetation restoration increased SOC and aggregate OC, and FR, MBC, LOC, and the physical protection of aggregates played important roles in regulating SOC and aggregate OC.

Positive responses of belowground C dynamics to nitrogen enrichment in China - Deng, Lei; Peng, Changhui; Zhu, Guangyu; Chen, Lei; Liu, Yulin; Shangguan, Zhouping (Science of The Total Environment, 2018)

Hydrologic and Edaphic Controls on Soil Carbon Emission in Dongting Lake Floodplain, China - Deng, Zhengmiao; Li, Youzhi; Xie, Yonghong; Peng, Changhui; Chen, Xinsheng; Li, Feng; Ren, Yijie; Pan, Baihan; Zhang, Chengyi (Journal of Geophysical Research: Biogeosciences, 2018)
Abstract Wetlands play a critical role in mitigating carbon emission. However, little is known about soil carbon emission and their environmental controls from inland floodplain wetlands. This study aimed to determine the effects of hydrologic and edaphic controllers (water table depth [ WTD ], soil temperature [ Ts ], and soil water content [ SWC ]) on soil C emission in Dongting Lake wetland, China. One‐year emissions were measured in Carex meadow and mudflat using static chambers during 2013 to 2014, including nonflooded season ( NFs ) and flooded season ( Fs ). The results showed that soil C emission in the Carex meadow and mudflat was 307.8 and 264.3 g C·m −2 ·year −1 , respectively, and 50–66% of soil C were emitted during NFs. Compared with NFs, CO 2 emission was significantly decreased by 57% but CH 4 emission was significantly increased by 38 times during Fs in the Carex meadow. Stepwise regression combined with structural equation model analysis showed that CO 2 and CH 4 flux were mainly influenced by Ts during NFs, and they were controlled by water temperature ( Tw ) during Fs. During NFs, CO 2 flux increased with increasing Ts and SWC but decreased significantly when SWC was over 66% and 52% in the Carex meadow and mudflat, respectively. CH 4 flux showed an emission pulse at SWC and Ts of 65% and 17.2 °C, respectively. These results indicate that flooding significantly inhibited soil CO 2 emission but stimulated CH 4 emission. The continuous decrease of flooding days caused by anthropogenic disturbances may induce soil C loss in Dongting Lake wetlands. , Key Points Soil C emission in Dongting Lake floodplain was 264.3–307.8 g C.m ‐2 .year ‐1 Flooding significantly inhibited soil CO 2 emission but stimulated CH 4 emission The decline of flooding days in Dongting Lake wetlands can potentially increase soil C loss

Estimates and Predictions of Methane Emissions from Wastewater in China from 2000 to 2020 - Du, Mingxi; Zhu, Qiuan; Wang, Xiaoge; Li, Peng; Yang, Bin; Chen, Huai; Wang, Meng; Zhou, Xiaolu; Peng, Changhui (Earth's Future, 2018)
Methane accounts for 20% of the global warming caused by greenhouse gases, and wastewater is a major anthropogenic source of methane. Based on the Intergovernmental Panel on Climate Change greenhouse gas inventory guidelines and current research findings, we calculated the amount of methane emissions from 2000 to 2014 that originated from wastewater from different provinces in China. Methane emissions from wastewater increased from 1349.01 to 3430.03 Gg from 2000 to 2014, and the mean annual increase was 167.69 Gg. The methane emissions from industrial wastewater treated by wastewater treatment plants ( E It ) accounted for the highest proportion of emissions. We also estimated the future trend of industrial wastewater methane emissions using the artificial neural network model. A comparison of the emissions for the years 2020, 2010, and 2000 showed an increasing trend in methane emissions in China and a spatial transition of industrial wastewater emissions from eastern and southern regions to central and southwestern regions and from coastal regions to inland regions. These changes were caused by changes in economics, demographics, and relevant policies. , Key Points Methane emission from wastewater from 2000 to 2014 was calculated to increase from 1349.01 Gg to 3430.03 Gg. Methane emission from wastewater from 2015 to 2020 was estimated to increase from 3875.30 Gg to 5212.75 Gg. A spatial transition of methane emission from wastewater was found and discussed in the present study.

Paleoceanography of northeastern Fram Strait since the last glacial maximum: Palynological evidence of large amplitude changes - Falardeau, Jade; De Vernal, Anne; Spielhagen, Robert F. (Quaternary Science Reviews, 2018)

Large-scale detection of vegetation dynamics and their potential drivers using MODIS images and BFAST: A case study in Quebec, Canada - Fang, Xiuqin; Zhu, Qiuan; Ren, Liliang; Chen, Huai; Wang, Kai; Peng, Changhui (Remote Sensing of Environment, 2018)

Palaeoclimate constraints on the impact of 2 °C anthropogenic warming and beyond - Fischer, Hubertus; Meissner, Katrin J.; Mix, Alan C.; Abram, Nerilie J.; Austermann, Jacqueline; Brovkin, Victor; Capron, Emilie; Colombaroli, Daniele; Daniau, Anne-Laure; Dyez, Kelsey A.; Felis, Thomas; Finkelstein, Sarah A.; et al. (Nature Geoscience, 2018)

Urban surface effects on current and future climate - Garuma, Gemechu Fanta; Blanchet, Jean-Pierre; Girard, Éric; Leduc, Martin (Urban Climate, 2018)

Two Types of Physical Inconsistency to Avoid with Univariate Quantile Mapping: A Case Study over North America Concerning Relative Humidity and Its Parent Variables - Grenier, Patrick (Journal of Applied Meteorology and Climatology, 2018)
Abstract Univariate quantile mapping (QM), a technique often used to statistically postprocess climate simulations, may generate physical inconsistency. This issue is investigated here by classifying physical inconsistency into two types. Type I refers to the attribution of an impossible value to a single variable, and type II refers to the breaking of a fixed intervariable relationship. Here QM is applied to relative humidity (RH) and its parent variables, namely, temperature, pressure, and specific humidity. Twelve sites representing various climate types across North America are investigated. Time series from an ensemble of ten 3-hourly simulations are postprocessed, with the CFSR reanalysis used as the reference product. For type I, results indicate that direct postprocessing of RH generates supersaturation values (>100%) at relatively small frequencies of occurrence. Generated supersaturation amplitudes exceed observed values in fog and clouds. Supersaturation values are generally more frequent and higher when RH is deduced from postprocessed parent variables. For type II, results show that univariate QM practically always breaks the intervariable thermodynamic relationship. Heuristic proxies are designed for comparing the initial bias with physical inconsistency of type II, and results suggest that QM generates a problem that is arguably lesser than the one it is intended to solve. When physical inconsistency is avoided by capping one humidity variable at its saturation level and deducing the other, statistical equivalence with the reference product remains much improved relative to the initial situation. A recommendation for climate services is to postprocess RH and deduce specific humidity rather than the opposite.

Biochar mitigates dissolved organic carbon loss but does not affect dissolved organic nitrogen leaching loss caused by nitrogen deposition in Moso bamboo plantations - Lei, Zhaofeng; Li, Quan; Song, Xinzhang; Wang, Weifeng; Zhang, Zhiting; Peng, Changhui; Tian, Linlin (Global Ecology and Conservation, 2018)

Multi-scale temporal variation of methane flux and its controls in a subtropical tidal salt marsh in eastern China - Li, Hong; Dai, Shengqi; Ouyang, Zutao; Xie, Xiao; Guo, Haiqiang; Gu, Caihong; Xiao, Xiangming; Ge, Zhenming; Peng, Changhui; Zhao, Bin (Biogeochemistry, 2018)

A critical analysis of the carbon neutrality assumption in life cycle assessment of forest bioenergy systems - Liu, Weiguo; Yu, Zhen; Xie, Xinfeng; Von Gadow, Klaus; Peng, Changhui (Environmental Reviews, 2018)
This study presents a critical analysis regarding the assumption of carbon neutrality in life cycle assessment (LCA) models that assess climate change impacts of bioenergy usage. We identified a complex of problems in the carbon neutrality assumption, especially regarding bioenergy derived from forest residues. In this study, we summarized several issues related to carbon neutral assumptions, with particular emphasis on possible carbon accounting errors at the product level. We analyzed errors in estimating emissions in the supply chain, direct and indirect emissions due to forest residue extraction, biogenic CO 2 emission from biomass combustion for energy, and other effects related to forest residue extraction. Various modeling approaches are discussed in detail. We concluded that there is a need to correct accounting errors when estimating climate change impacts and proposed possible remedies. To accurately assess climate change impacts of bioenergy use, greater efforts are required to improve forest carbon cycle modeling, especially to identify and correct pitfalls associated with LCA accounting, forest residue extraction effects on forest fire risk and biodiversity. Uncertainties in accounting carbon emissions in LCA are also highlighted, and associated risks are discussed.

Application of machine-learning methods in forest ecology: recent progress and future challenges - Liu, Zelin; Peng, Changhui; Work, Timothy; Candau, Jean-Noel; DesRochers, Annie; Kneeshaw, Daniel (Environmental Reviews, 2018)
Machine learning, an important branch of artificial intelligence, is increasingly being applied in sciences such as forest ecology. Here, we review and discuss three commonly used methods of machine learning (ML) including decision-tree learning, artificial neural network, and support vector machine and their applications in four different aspects of forest ecology over the last decade. These applications include: (i) species distribution models, (ii) carbon cycles, (iii) hazard assessment and prediction, and (iv) other applications in forest management. Although ML approaches are useful for classification, modeling, and prediction in forest ecology research, further expansion of ML technologies is limited by the lack of suitable data and the relatively “higher threshold” of applications. However, the combined use of multiple algorithms and improved communication and cooperation between ecological researchers and ML developers still present major challenges and tasks for the betterment of future ecological research. We suggest that future applications of ML in ecology will become an increasingly attractive tool for ecologists in the face of “big data” and that ecologists will gain access to more types of data such as sound and video in the near future, possibly opening new avenues of research in forest ecology.

Australian snowpack in the NARCliM ensemble: evaluation, bias correction and future projections - Luca, Alejandro Di; Evans, Jason P.; Ji, Fei (Climate Dynamics, 2018)

Quaternary dinoflagellate cysts in the Arctic Ocean: Potential and limitations for stratigraphy and paleoenvironmental reconstructions - Matthiessen, Jens; Schreck, Michael; De Schepper, Stijn; Zorzi, Coralie; De Vernal, Anne (Quaternary Science Reviews, 2018)

Arctic environmental change beyond instrumental records: introduction and overview - Ó Cofaigh, Colm; Kirchner, Nina; Fedorov, Grigory; Noormets, Riko; De Vernal, Anne (arktos, 2018)

Data supporting assessment for nitrous oxide emissions from soils under traditional cropland and apple orchard in the Loess Plateau of China - Pang, Junzhu; Wang, Xiaoke; Peng, Changhui; Mu, Yujing; Ouyang, Zhiyun; Lu, Fei; Zhang, Hongxing; Zhang, Shuoxin; Liu, Wenzhao (Data in Brief, 2018)

Independently assessing the representation of midlatitude cyclones in high‐resolution reanalyses using satellite observed winds - Pepler, Acacia S.; Di Luca, Alejandro; Evans, Jason P. (International Journal of Climatology, 2018)
ABSTRACT High‐resolution reanalyses offer the potential to improve our understanding of midlatitude cyclones, particularly smaller‐scale systems and those with complex structures. However, previous studies have demonstrated large variations in the frequency and characteristics of Australian midlatitude cyclones between reanalyses when using their native resolution. In this paper we use satellite observations of winds and rainfall in order to evaluate the ability of the ERA‐Interim, JRA55, MERRA and CFSR reanalyses to reproduce Australian east coast cyclones. The MERRA reanalysis produces a large number of erroneous small‐scale lows without cyclonic wind patterns using a simple pressure‐difference‐based cyclone identification and tracking method. Consequently, we recommend the ERA‐Interim reanalysis when using such methods, or applying more complex tracking methods that are able to compensate for these issues.

Investigating added value of regional climate modeling in North American winter storm track simulations - Poan, E. D.; Gachon, P.; Laprise, R.; Aider, R.; Dueymes, G. (Climate Dynamics, 2018)

Spatial modeling of daily concentrations of ground-level ozone in Montreal, Canada: A comparison of geostatistical approaches - Ramos, Yuddy; Requia, Weeberb J.; St-Onge, Benoît; Blanchet, Jean-Pierre; Kestens, Yan; Smargiassi, Audrey (Environmental Research, 2018)

Dynamical downscaling with the fifth-generation Canadian regional climate model (CRCM5) over the CORDEX Arctic domain: effect of large-scale spectral nudging and of empirical correction of sea-surface temperature - Takhsha, Maryam; Nikiéma, Oumarou; Lucas-Picher, Philippe; Laprise, René; Hernández-Díaz, Leticia; Winger, Katja (Climate Dynamics, 2018)

The Global N2O Model Intercomparison Project - Tian, Hanqin; Yang, Jia; Lu, Chaoqun; Xu, Rongting; Canadell, Josep G.; Jackson, Robert B.; Arneth, Almut; Chang, Jinfeng; Chen, Guangsheng; Ciais, Philippe; Gerber, Stefan; Ito, Akihiko; et al. (Bulletin of the American Meteorological Society, 2018)
Abstract Nitrous oxide (N 2 O) is an important greenhouse gas and also an ozone-depleting substance that has both natural and anthropogenic sources. Large estimation uncertainty remains on the magnitude and spatiotemporal patterns of N 2 O fluxes and the key drivers of N 2 O production in the terrestrial biosphere. Some terrestrial biosphere models have been evolved to account for nitrogen processes and to show the capability to simulate N 2 O emissions from land ecosystems at the global scale, but large discrepancies exist among their estimates primarily because of inconsistent input datasets, simulation protocol, and model structure and parameterization schemes. Based on the consistent model input data and simulation protocol, the global N 2 O Model Intercomparison Project (NMIP) was initialized with 10 state-of-the-art terrestrial biosphere models that include nitrogen (N) cycling. Specific objectives of NMIP are to 1) unravel the major N cycling processes controlling N 2 O fluxes in each model and identify the uncertainty sources from model structure, input data, and parameters; 2) quantify the magnitude and spatial and temporal patterns of global and regional N 2 O fluxes from the preindustrial period (1860) to present and attribute the relative contributions of multiple environmental factors to N 2 O dynamics; and 3) provide a benchmarking estimate of N 2 O fluxes through synthesizing the multimodel simulation results and existing estimates from ground-based observations, inventories, and statistical and empirical extrapolations. This study provides detailed descriptions for the NMIP protocol, input data, model structure, and key parameters, along with preliminary simulation results. The global and regional N 2 O estimation derived from the NMIP is a key component of the global N 2 O budget synthesis activity jointly led by the Global Carbon Project and the International Nitrogen Initiative.

CH4 concentrations and fluxes in a subtropical metropolitan river network: Watershed urbanization impacts and environmental controls - Wang, Xiaofeng; He, Yixin; Chen, Huai; Yuan, Xingzhong; Peng, Changhui; Yue, Junsheng; Zhang, Qiaoyong; Zhou, Lilei (Science of The Total Environment, 2018)

The linkage between vegetation and soil nutrients and their variation under different grazing intensities in an alpine meadow on the eastern Qinghai-Tibetan Plateau - Yang, Zhenan; Zhu, Qiuan; Zhan, Wei; Xu, Yingyi; Zhu, Erxiong; Gao, Yongheng; Li, Shiqing; Zheng, Qunying; Zhu, Dan; He, Yixin; Peng, Changhui; Chen, Huai (Ecological Engineering, 2018)

Individual and combined effects of multiple global change drivers on terrestrial phosphorus pools: A meta-analysis - Yue, Kai; Yang, Wanqin; Peng, Yan; Peng, Changhui; Tan, Bo; Xu, Zhenfeng; Zhang, Li; Ni, Xiangyin; Zhou, Wei; Wu, Fuzhong (Science of The Total Environment, 2018)

Soil CH4 and CO2 dynamics and nitrogen transformations with incubation in mountain forest and meadow ecosystems - Zhang, Junjun; Peng, Changhui; Xue, Wei; Yang, Zhenan; Yang, Bin; Li, Peng; Zhu, Qiuan; Wang, Meng (CATENA, 2018)